Calibration Tests For Underwater Acoustic Transponders Using Kalman Filter - Mahmud, Mohd Razali (Fakulti Ukur dan Harta Tanah, 1995)
Two tests were carried out for the calibration of underwater acoustic transponders using Kalman filter. Both tests used the Long Baseline Acoustic Positioning method. The first test is known as the relative calibration test and uses observables only from underwater acoustic transponders. This test is for the adjustment of the shape and scale of the transponder array. It requires at least three coordinates to be fixed. The second test, known as the absolute calibration test, involves the observables from four systems (i.e. DGPS, underwater acoustic system, range-range system and hyperbolic system) integrated together to give geodetic position and orientation to the transponder array. The results of both tests are presented.